Formulation And Evaluation Of Biphasic Drug Delivery System Of Terbutaline Sulphate For Chronotherapy - Dr.N. G. RAGHAVENDRA RAO; HARSH PANCHAL; MOHD ABDUL HADI (International Journal of Pharma and Bio Sciences, 2012)
Terbutaline sulphate is a β2-adrenergic agonist bronchodilator used to treat bronchospasm (wheezing, shortness of breath) associated with lung diseases such as asthma, bronchitis, and emphysema. Bioavailability of terbutaline sulphate about 14.8 %. The drug half life is 3-4 hrs.. So in order to improve the bioavailability and efficacy we have designed granules and tablets filled in HPMC capsule system, which is presented as a biphasic delivery system. The outer layer that fills the void spaces between the mini-tablets was formulated to release the drug in a very short time (fast release), while the mini-tablets provided a sustain release. Fast releasing component comprises superdisintegrant croscarmellose sodium, while mini-tablet was formulated using different concentration of HPMC and Ethyl cellulose to obtain different drug release rates. The In-vitro performance of these systems showed the desired biphasic behaviour. The drug contained in the fast releasing phase (Granular powder) dissolved within the first 5 min, whereas the drug contained in the mini-tablets was released at different rates, depending upon composition of mini tablets. The prepared tablets were subjected for post-compression parameters. The compatibility of drug with other ingredients was checked by FTIR and DSC studies. FTIR and DSC results revealed that there was no interaction between drug and other excipients. All the pre and post-compressional Parameters were evaluated and the results were within acceptable limits. The in-vitro performance of our best tablet filled HPMC capsule system showed the desired behavior, the drug contained in the granules for immediate release dissolved within the first 5 min, whereas the drug contained in the sustained release tablets was released over a period of 10 to 12 hrs. Based on the release kinetic parameters calculated, it can be concluded that tablets containing HPMC and EC were particularly suitable approaching to sustain or prolong release over 10-12 hrs time periods. From this, study it can be concluded that, granules and tablets filled in HPMC capsule systems containing Terbutaline sulphate shows that both sustained release as well as immediate release may improve the bioavailability and efficacy.